Praktik akuntansi lingkungan pada sektor ekonomi kreatif Indonesia: Studi niat perilaku UMKM milenial - Muhammad Alfarizi (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2023)
Global environmental problems are receiving increasing attention from academics, policymakers, regulators, activists, and the public. Although economically significant, Indonesian Micro, Small, and Medium Enterprises (MSME) are the main contributors to environmental pollution. Environmental Accounting (EA) calculates the cost of the environmental impact of business operations. However, it is unclear whether environmental impact costs have been calculated in traditional accounting. The millennial generation dominates MSME owners in Indonesia. This study analyzes the factors that encourage the intention of millennial MSME owners to apply Environmental Accounting Practices. This study uses the theory of planned behavior and an online survey with 164 respondents. Data analysis using PLS-SEM. The results show that the benefits of environmental accounting, price, complex integration, and subjective norms affect the attitude of millennial MSME owners toward environmental accounting. The price and complexity of integration encourage millennial MSME owners to control their behavior. Organizational environmental regulations and orientation have no significant effect. Subjective norms, attitudes, and behavioral controls affect the behavioral intention of environmental accounting in millennial generation MSMEs. These findings are essential for MSME owners, policymakers, MSME associations, and Indonesian academics.